Inflammasome Priming in Sterile Inflammatory Disease. Issue 2 (February 2017) - Patel, Meghana N.; Carroll, Richard G.; Galván-Peña, Silvia; Mills, Evanna L.; Olden, Robin; Triantafilou, Martha; Wolf, Amaya I.; Bryant, Clare E.; Triantafilou, Kathy; Masters, Seth L.
Abstract : The inflammasome is a cytoplasmic protein complex that processes interleukins (IL)-1β and IL-18, and drives a form of cell death known as pyroptosis. Oligomerization of this complex is actually the second step of activation, and a priming step must occur first. This involves transcriptional upregulation of pro-IL-1β, inflammasome sensor NLRP3, or the non-canonical inflammasome sensor caspase-11. An additional aspect of priming is the post-translational modification of particular inflammasome constituents. Priming is typically accomplished in vitro using a microbial Toll-like receptor (TLR) ligand. However, it is now clear that inflammasomes are activated during the progression of sterile inflammatory diseases such as atherosclerosis, metabolic disease, and neuroinflammatory disorders. Therefore, it is time to consider the endogenous factors and mechanisms that may prime the inflammasome in these conditions. Trends: NLRP3 inflammasome priming requires transcriptional upregulation of NLRP3 and pro-IL-1β expression, together with post-translational modification of NLRP3 itself. Obesity and other chronic inflammatory states prime the NLRP3 inflammasome, and these constitute serious predisposing factors for inflammasome activation in sterile inflammatory disease. Microbial priming of the inflammasome could potentially drive crosstalk between the environment and the development of autoinflammatory disease. Inflammasome priming is not limited to immune cells, and can contribute significantly to overall pathology during chronic, low-grade inflammation.